Genetic Manipulation of Calcium Release-Activated Calcium Channel 1 Modulates the Multipotency of Human Cartilage-Derived Mesenchymal Stem Cells. (17th February 2019) - Liu, Shuang; Takahashi, Minae; Kiyoi, Takeshi; Toyama, Kensuke; Mogi, Masaki
Abstract : Calcium is a ubiquitous intracellular messenger that has a crucial role in determining the proliferation, differentiation, and functions of multipotent mesenchymal stem cells (MSCs). Our study is aimed at elucidating the influence of genetically manipulating Ca 2+ release-activated Ca 2+ (CRAC) channel-mediated intercellular Ca 2+ signaling on the multipotency of MSCs. The abilities of genetically engineered MSCs, including CRAC-overexpressing and CRAC-knockout MSCs, to differentiate into multiple mesenchymal lineages, including adipogenic, osteogenic, and chondrogenic lineages, were evaluated. CRAC channel-mediated Ca 2+ influx into these cells was regulated, and the differentiation fate of MSCs was modified. Upregulation of intracellular Ca 2+ signals attenuated the adipogenic differentiation ability and slightly increased the osteogenic differentiation potency of MSCs, whereas downregulation of CRACM1 expression promoted chondrogenic differentiation potency. The findings demonstrated the effects of genetically manipulating MSCs by targeting CRACM1. CRAC-modified MSCs had distinct differentiation fates to adipocytes, osteoblasts, and chondrocytes. To aid in the clinical implementation of tissue engineering strategies for joint regeneration, these data may allow us to identify prospective factors for effective treatments and could maximize the therapeutic potential of MSC-based transplantation.